Microstructure of Whole Wheat versus White Flour and Wheat-Chickpea Flour Blends and Dough: Impact on the Glycemic Response of Pan Bread - Tasleem A. Zafar; Ahmed Aldughpassi; Abdulwahab Al-Mussallam; Amani Al-Othman (International Journal of Food Science)
Whole foods are generally considered healthier choices compared to processed foods. For nutritional consideration, whole wheat bread is recommended over the white bread. However, it has a similarly high effect on glycemic response (GR) as the white bread. This study is aimed at assessing the microstructure of whole wheat flour (WWF), white flour (WF), chickpea flour (BF), their blends, and dough and the GR of the bread made thereof. Scanning electron microscope analysis showed clear distinctions in the microstructure of the three flours. WWF particle size distribution had the widest spread with a polydispersity index (PDI) of 1.0 (±0.0) and wider average diameter, with z value of 1679.5 (±156.3) compared with the particle size of 658.9 (±160.4) and PDI of 0.740 (±0.04) for WF followed by BF with the particle size of 394.1 (±54.9) and PDI of 0.388 (±0.07) (p<0.05). The falling number was significantly (p<0.05) lower for WWF compared to WF or BF, indicating higher alpha-amylase activity. Thus, bread made from WWF without BF substitution exhibited a higher glycemic response similar to the bread made from WF. When partly replaced with BF, the GR of the bread made with WWF or WF reduced significantly (p<0.05) in healthy individuals.